EFEKTIVITAS PEMBELAJARAN PRAKTIK PEMESINAN BUBUT MENGGUNAKAN PENDEKATAN STEM - Rozikin, Rozikin; Abizar, Haris; Ikhsanudin, Ikhsanudin (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
21st century learning demands mastery of knowledge that connects science, technology, engineering and mathematics which play a major role as a learning reform towards 21st century learning. However, in the learning process, students are still not accustomed to connecting the four fields of exact sciences which are considered effective in addressing learning needs in the 21st century. The research aims to describe and describe the effectiveness of the STEM Approach that has been applied to learning lathe machining practices at SMK. This research was conducted at 13 vocational schools spread across Cilegon City, Serang City, and Serang Regency using the ex-post facto research method. Data were collected using Simple Random Sampling technique. A total of 32 samples of teachers who teach lathe machining techniques. The research instrument used a questionnaire that had validity and reliability testing. The results of testing the research hypothesis are the effectiveness and relationship between the use of the STEM approach and Lathe Machining Practice Learning. This is evidenced by the implementation of STEM declared “Good” and the effectiveness of STEM can be categorized as “Very Effective”. There is a relationship between the STEM variable (X) and the lathe machining variable (Y) by looking at the value in the T-test results which show that tcount 3.048> ttable 2.042 and significance <0.05, it can be concluded that there is an effectiveness of lathe machining learning using the STEM approach according to the specified hypothesis